Penerapan Model Pembelajaran Discovery Learning Dengan Pendekatan Saintifik Terhadap Peningkatan Hasil Belajar Siswa Kelas XI SMAN 9 Maros - Mardhaatillah Chumaerah; Ulfa Dira Azhari (Journal Innovation In Education, 2024)
The use of learning models can also be a factor that determines students' learning success. If the learning model used is appropriate, it can arouse students' interest in studying the material being taught in such a way that it influences the quality of learning outcomes. So the teacher must be able to create a learning model that creates a situation where the class of students can be active in the learning process. This research was carried out using the Classroom Action Research (PTK) method. Wardani & Wihardit (2018) stated that PTK is research conducted by a teacher in the class he teaches which aims to improve student learning outcomes. The subjects of this research were 36 students in class XI MIPA 3, consisting of 11 male students and 15 female students. P2K implementation is carried out in 2 cycles. The results of classroom action research using the Discovery Learning model with a scientific approach for two cycles, the results obtained are: First, the application of the Discovery Learning learning model with a scientific approach can improve students' science learning outcomes in class XI SMAN 9 Maros. Second, the application of the Discovery learning model Learning with an effective scientific approach can increase liveliness and activity in the teaching and learning process in accordance with observations of students' attitudes during the implementation of classroom action research in cycle I and cycle II.